The Effect of Spatial Hindrance on Stereoselective Synthesis of Real Enaminoesters and Determination of the Relative Stability of the Two E- and Z-Isomers of Hypothetical Enaminoesters. (26th May 2020) - Ghodsi, Fatemeh; Shahraki, Mehdi; Habibi-Khorassani, Sayyed Mostafa; Nassiri, Mahmoud; Fazilatkhah, Malihe
Abstract: The three-component reactions of isoquinoline and acetylenic esters in the presence of 2-tert-butyl-4-methylphenol has been investigated. The reactions were proceeded smoothly at room temperature without the usage of a catalyst. The structures of the synthesized compounds were characterized by elemental analyses and spectral studies. Also, quantum mechanical calculations were carried out using the ab initio and DFT methods at the HF/6-31G (d, p) and B3LYP/6-31G (d, p) levels of theory to determine the stability of the two E and Z- isomers from both the hypothetical and real reactions between phenantridine or isoquinoline and dimethyl acetylendicarboxylate in the presence of phenol derivatives for the generation of enaminoesters, in both gas phase and solvent media (polar and nonpolar). The results showed that more effective hindrance of any reactants (phenol derivatives, acetylenic esters and phenantridine or isoquinoline) should be considered for the generation of highly stereoselective enaminoester ( E -isomer) in real or hypothetical synthesis. To reduce the effect of spatial hindrance on all cases (real or hypothetical synthesis) of E -enaminoester, corresponding to its more stability, the hydrogen atom and phenanthridine (or isoquinoline) moieties were positioned on the side of the double bond within the structure of an enaminoester. The E- isomers were recognized as the preferential form of the highly stable enaminoester and they can be considered as an effective product that has biological activity.